2011
DOI: 10.1038/mp.2011.149
|View full text |Cite
|
Sign up to set email alerts
|

Adult attention-deficit hyperactivity disorder is associated with alterations in circadian rhythms at the behavioural, endocrine and molecular levels

Abstract: Attention-deficit hyperactivity disorder (ADHD) in adults is associated with impaired sleep, and it has been postulated that this impairment may contribute to the psychopathology of this common condition. One key driver of sleep/wake cycles is the circadian system, which at the molecular level consists of a series of transcriptional feedback loops of clock genes, which in turn produce endocrine, physiological and behavioural outputs with a near 24 h periodicity. We set out to examine circadian rhythms at the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
144
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 29 publications
19
144
2
8
Order By: Relevance
“…Por último, los trastornos de sueño se anales de psicología, 2014, vol. 30, nº 3 (octubre) han relacionado con mutaciones en los genes Per2 y Per3 (Cermakian y Boivin, 2003) y el TDAH con mutaciones en el gen Per2 (Baird, Coogan, Siddiqui, Donev y Thome, 2012).…”
Section: Discussionunclassified
“…Por último, los trastornos de sueño se anales de psicología, 2014, vol. 30, nº 3 (octubre) han relacionado con mutaciones en los genes Per2 y Per3 (Cermakian y Boivin, 2003) y el TDAH con mutaciones en el gen Per2 (Baird, Coogan, Siddiqui, Donev y Thome, 2012).…”
Section: Discussionunclassified
“…Of note, adult ADHD is linked with blunted Per2 expression (Baird et al, 2012). It is also interesting that the other clock genes with altered circadian profiles in ENT1 KO mice, Clock and Dbp, are associated with ADHD (Kissling et al, 2008;Roybal et al, 2007;Xu et al, 2010), bipolar disorder (Le-Niculescu et al, 2008;Lee et al, 2010;Shi et al, 2008;Soria et al, 2010), anxiety (Le-Niculescu et al, 2011a), and AUD (Le-Niculescu et al, 2011b;Le-Niculescu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While clock gene variants are not among the strongest associations with ADHD found by GWAS, clock gene variants may be enriched among weaker GWAS associations [58]. A gene expression study from subjects with adult ADHD revealed a number of alterations in molecular rhythms [66], including loss of BMAL and PER2 expression rhythms in oral mucosal cells, blunted melatonin rhythms, and 3 hr phase delays in cortisol rhythms relative to controls. Consistent with previous behavioral reports, the same study also found high levels of activity at night, greater evening preference, and long latency to sleep onset.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%